2021
DOI: 10.3389/fgene.2021.615655
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage M2 Co-expression Factors Correlate With the Immune Microenvironment and Predict Outcome of Renal Clear Cell Carcinoma

Abstract: Purpose: In the tumor microenvironment, the functional differences among various tumor-associated macrophages (TAM) are not completely clear. Tumor-associated macrophages are thought to promote the progression of cancer. This article focuses on exploring M2 macrophage-related factors and behaviors of renal clear cell carcinoma.Method: We obtained renal clear cell carcinoma data from TCGA-KIRC-FPKM, GSE8050, GSE12606, GSE14762, and GSE3689. We used the “Cibersort” algorithm to calculate type M2 macrophage propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…In this context, it did not escape our attention that mouse Vav1-Myo1f pre-lymphoma samples were specifically enriched in a TAM-associated signature, supporting an early crosstalk between Vav1-Myo1f -expressing CD4 + T cells and the tumor microenvironment implicated in tumor initiation. In human PTCL, the presence of tumor-infiltrating myeloid cells, including TAMs, has been associated with poor prognosis, suppression of anti-tumor responses, and limited response to initial therapy ( Allavena et al, 2021 ; Skytthe et al, 2020 ; Wang et al, 2021 ). Here we show that in vivo depletion of macrophages inhibits Vav1-Myo1f CD4 + lymphoma cell proliferation and survival, demonstrating a close interdependency between lymphoma cells and TAM and supporting a role for TAM-directed targeted therapies for the treatment of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it did not escape our attention that mouse Vav1-Myo1f pre-lymphoma samples were specifically enriched in a TAM-associated signature, supporting an early crosstalk between Vav1-Myo1f -expressing CD4 + T cells and the tumor microenvironment implicated in tumor initiation. In human PTCL, the presence of tumor-infiltrating myeloid cells, including TAMs, has been associated with poor prognosis, suppression of anti-tumor responses, and limited response to initial therapy ( Allavena et al, 2021 ; Skytthe et al, 2020 ; Wang et al, 2021 ). Here we show that in vivo depletion of macrophages inhibits Vav1-Myo1f CD4 + lymphoma cell proliferation and survival, demonstrating a close interdependency between lymphoma cells and TAM and supporting a role for TAM-directed targeted therapies for the treatment of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…All of these results imply that FUCA1/FUCA2 may be acting in a tumor-suppressive role, and lower expression of FUCA1/FUCA2 prognosticates worse pathological results, less therapeutic effect, and shorter PFI. This finding is consistent with many previous studies, which further validate the reliability of our conclusion (12,13,(21)(22)(23).…”
Section: Discussionsupporting
confidence: 94%
“…We generated signatures of M0/M1/M2 phenotypes and found that STOSE tumors were enriched with M2 TAMs [F13a1 (27), Fabp5 (28), S100a4 and Arg1 (26); Supplementary Fig. S2; Supplementary Table S5; ref .…”
Section: Ose-derived Stose Tumors Express Mhc-i and Are Preferentiall...mentioning
confidence: 99%